The Embedding Theorem of an L0-Prebarreled Module into Its Random Biconjugate Space. (30th April 2017) - Zhang, Xia; Liu, Ming
Abstract : We first prove Mazur's lemma in a random locally convex module endowed with the locally L 0 -convex topology. Then, we establish the embedding theorem of an L 0 -prebarreled random locally convex module, which says that if ( S, P ) is an L 0 -prebarreled random locally convex module such that S has the countable concatenation property, then the canonical embedding mapping J of S onto J ( S ) ⊂ ( S s ⁎ ) s ⁎ is an L 0 -linear homeomorphism, where ( S s ⁎ ) s ⁎ is the strong random biconjugate space of S under the locally L 0 -convex topology.